2020
DOI: 10.21873/anticanres.14149
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Is Involved in Sunitinib and Sorafenib Resistance in Renal Cell Carcinoma

Abstract: Background/Aim: Targeted receptor tyrosine kinase inhibitor (TKI) is a standard treatment in advanced renal cell carcinoma (RCC). However, the role of PTEN in TKI resistance remains poorly understood. We aimed to determine the functional role of PTEN knockout and analyse the predictive significance of PTEN expression for TKI treatment in RCC. Materials and Methods: We developed PTEN knockout cells in RCC cell lines using the CRISPR-Cas9 system and analysed the effect of PTEN knockout on spheroid formation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…Hafsi et al (2012) then summarized the crucial role of PI3 k/PTEN/Akt pathway in the formation of drug resistance due to its role of regulating cell growth. What is more, Sekino et al (2020) proved that knocking out PTEN could decrease the sensitivity to both sunitinib and sorafenib in RCC cells, which indicated the active participation of PTEN-related pathway in regulating cell responses to targeted agents. These findings were consistent with our result in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Hafsi et al (2012) then summarized the crucial role of PI3 k/PTEN/Akt pathway in the formation of drug resistance due to its role of regulating cell growth. What is more, Sekino et al (2020) proved that knocking out PTEN could decrease the sensitivity to both sunitinib and sorafenib in RCC cells, which indicated the active participation of PTEN-related pathway in regulating cell responses to targeted agents. These findings were consistent with our result in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…EEF1E1 is a scaffold of the macromolecule aminoacyl tRNA synthase complex, which mediates ATM/ATR-mediated p53 activation as a protective factor of prognosis (Yu et al, 2017;Biterge-Sut, 2019). MAPT plays an important role in the assembly of tubulin and stabilization of microtubules, which act as protective factors in renal and prostate cancers (Han et al, 2020;Sekino et al,…”
Section: Discussionmentioning
confidence: 99%
“…FLT3, a class III receptor tyrosine kinase, drives cellular proliferation through activation of the MAPK, PI3K, and STAT5 signaling pathways (Takahashi, 2011). MAPT, mainly expressed in neuronal cells, lymphocytes, and epithelial cells, is associated with survival in prostate cancer and promotes bicalutamide resistance (Sekino et al, 2020). Multiple studies have demonstrated that TNFRSF4 can work as a therapeutic agent and play a significant role in immunotherapy of preclinical FIGURE 7 | The risk signature is closely related to CD8 + T cells infiltration and PDL1 expression of HCC.…”
Section: Discussionmentioning
confidence: 99%